THE PRACTICE OF SUFISM BY THREE ULAMA (AL GHAZALI, AL QUSYAIRI, MUHYIDIN IBNU ‘ARABI) - Putri Arumsari, Ai (Bahasa Indonesia, 2026)
This study contains an explanation of the practice of Sufism. This study focuses on three main figures with different approaches to Sufism: Imam Al-Ghazali, Imam Al-Qusyairi, and Muhyiddin Ibn ‘Arabi. Each figure has a unique Sufism practice, based on personal spiritual experiences that are esoteric and difficult to explain rationally. Imam Al-Ghazali emphasized the importance of dhikr, night prayer, and riyadhah for the purification of the soul and the formation of morals, as explained in Ihya' Ulumuddin. Meanwhile, Imam Al- Qusyairi, through his works Risalah al-Qusyairiyyah and Tafsir Al-Qusyairi Lathaif al- Isyarat, prioritized dhikr and jihad an-nafs as the core of his Sufism. Muhyiddin Ibn 'Arabi emphasized intensive dhikr as part of the path of mujahadah, which led to spiritual experiences and a broad understanding of metaphysics. However, limited sources pose a challenge in uncovering the full range of Sufism practices of each figure, particularly Imam Al-Qusyairi and Ibn 'Arabi. Therefore, this study only presents practices that can be verified through authoritative references, to maintain the accuracy and objectivity of the analysis.